Peningkatan Kompetensi Menyusun Legal Drafting Bagi Aparatur dan Badan Permusyawaratan Desa di Desa Cigugurgirang: Competency Improvement in Drafting Regulations for Village Officials and Consultative in Cigugurgirang Village - Ajeng Ayu Milanti; Sumiyati; Sulistia Suwondo; Ita Susanti; M. Yunus Maulana (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
Village regulations are a crucial instrument in governing sustainable development at the village level, ensuring justice, and safeguarding the rights of local communities. These regulations grant authority to village officials and the Village Consultative Body. However, initial observations revealed that 66.7% of them were not familiar with the procedures for drafting village regulations. This undoubtedly poses a significant risk, as the resulting regulatory products may not reflect the actual needs and interests of the village community. Therefore, this community engagement program aims to provide training to enhance the competence of village officials and the Village Consultative Body in drafting village regulations in Cigugur Girang Village. The training was conducted in July 2023 at the village office hall. The implementation method consisted of training and mentoring for a total of 40 hours over 7 days. The training was attended by 20 participants, including village officials and members of the Village Consultative Body. Based on the evaluation of the training activities, there was a 57.1% improvement in understanding and technical skills in drafting village regulations. This was demonstrated by the creation of four new draft village regulations during the training. These four draft village regulations align with the actual needs of the village community, making them suitable regulatory products to be enacted by the village government. Keywords:  Village-Regulations; Village-Officials; Village-Consultative (BPD); Drafting; Village.. ABSTRAKT Legal Drafting merupakan instrumen penting dalam tata kelola pembangunan dan pengembangan tingkat desa secara berkelanjutan, yang memastikan keadilan dan melindungi hak-hak masyarakat lokal. Peraturan tersebut menjadi wewenang bagi aparatur dan badan permusyawaratan desa. Namun, pada hasil observasi awal diketahui bahwa sebesar 66.7% belum mengetahui tata cara pembuatan Legal Drafting. Hal ini tentunya dapat memberi resiko besar, manakala produk regulasi yang dihasilkan tidak mencerminkan kebutuhan dan kepentingan aktual dari masyarakat desa. Oleh karena itu, program pengabdian kepada masyarakat ini ditujukan untuk memberikan pelatihan dalam upaya meningkatkan kompetensi menyusun Legal Drafting bagi aparatur dan badan permusyawaratan desa di Desa Cigugurgirang. Pelatihan diselenggarakan pada bulan Juli 2023 bertempat di gedung aula kantor desa. Metode pelaksanaan yakni dalam bentuk pelatihan dan pendampingan selama 40 jam dalam waktu 7 hari kegiatan. Pelaksanaan pelatihan diikuti oleh 20 orang peserta yang merupakan aparatur dan anggota badan permusyawaratan desa. Berdasarkan penilaian hasil evaluasi kegiatan pelatihan terdapat peningkatan pemahaman dan teknis keterampilan penyusunan Legal Drafting sebesar 85.7%. Hal ini terbukti dari terbentuknya empat draft Legal Drafting baru saat pelatihan. Keempat Legal Drafting tersebut sesuai dengan kebutuhan aktual masyarakat desa sehingga draft peraturan tersebut dapat menjadi produk regulasi yang ditetapkan oleh pemerintah desa tersebut.